Selection of a South African Heterorhabditis bacteriophora Isolate for in vitro Liquid Mass Production for the Control of Thaumatotibia leucotreta in Grapevine: n/a - Claasen, N.J.; Dunn, M.D.; Malan, A.P. (South African Journal of Enology and Viticulture, 2024)
The South African table grape industry requires biological control options for pest insects to maintain export relationships. Entomopathogenic nematodes (EPNs) has shown effective biological control of the economically important table grape pest, Thaumatotibia leucotreta, the false codling moth (FCM). Critical to the success of EPNs is their ability to be mass produced using in vitro liquid mass production methods. The selection of suitable isolates for mass production is the most important step in the process of developing an EPN biocontrol product for commercial purposes. Heterorhabditis bacteriophora is the most common EPN species found in South African soils, with previous research having shown its high pathogenicity against a variety of grapevine pest insects. In this study, four local H. bacteriophora isolates were laboratory-screened to select the best candidate in terms of virulence against FCM, and differences in the symbiotic bacteria isolates were also observed. Two of the H. bacteriophora isolates, CRI_LC and LLM’s symbiotic Photorhabdus bacteria, showed slight bioluminescence, while SGI_170 and Px_SPH showed strong luminescence, indicating the biological difference between the symbiotic bacterial species that are associated with the same nematode species. Molecular analysis of the 16S gene indicate three different bacterial species, of which two were the same and two are possibly new. The H. bacteriophora isolate, SGI_170, which showed the highest virulence against late-instar FCM larvae, was chosen for the further development of in vitro liquid culture.